Multi-level feedback based time synchronization algorithm for wireless sensor networks - HUANGFU Wei1; ZHOU Xin-yun1; CHEN Can-feng3 (Tongxin xuebao)
Aiming at the fast and efficient time synchronization protocol for the wireless sensor networks under resource constraints, a novel feedback-based full-scale time synchronization（FTS） algorithm was proposed.The basic idea of FTS is to execute iteratively time synchronization downlink operations on all the nodes of the wireless sensor network and collect the two-way path delay information from only a part of nodes to calculate the average delay adjustment per hop.The stochastically feedback scheme is adopted to reduce the uplink packets.The FTS algorithm also consists of the mechanisms of synchronization error monitoring and clock skew correction.The FTS was implemented on the popular TelosB sensor nodes from UC Berkeley.The experiments show that FTS is a fast, resource-efficient algorithm with ra-tional synchronization precision.